2005
DOI: 10.1124/mol.105.017954
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Modulation of P-Glycoprotein-Mediated Transport at the Blood-Brain Barrier by Tumor Necrosis Factor-α and Lipopolysaccharide

Abstract: At the blood-brain barrier, P-glycoprotein, an ATP-driven drug efflux pump, selectively limits drug access to the brain parenchyma, impeding pharmacotherapy of a number of central nervous system (CNS) disorders. We previously used confocal imaging to demonstrate in isolated rat brain capillaries that endothelin-1 (ET-1), acting through an ET B receptor, NO synthase, and protein kinase C, rapidly and reversibly reduces P-glycoprotein transport function. In this study, we define a link between the brain's innate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
236
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 184 publications
(249 citation statements)
references
References 27 publications
12
236
1
Order By: Relevance
“…19 The procedure would also allow a transient decrease in the function of the Pgp pump, thereby allowing for improved delivery of chemotherapy agents that are also known substrate of this pump. 22 Even if the barrier is breached in the tumoral tissue, its integrity remains virtually intact at the periphery of the tumor. 19 Sato et al 20 elegantly demonstrated in vivo that the mannitol infusion increases the permeability of the barrier at the edge of the tumor, in the peritumoral area.…”
Section: Figurementioning
confidence: 99%
“…19 The procedure would also allow a transient decrease in the function of the Pgp pump, thereby allowing for improved delivery of chemotherapy agents that are also known substrate of this pump. 22 Even if the barrier is breached in the tumoral tissue, its integrity remains virtually intact at the periphery of the tumor. 19 Sato et al 20 elegantly demonstrated in vivo that the mannitol infusion increases the permeability of the barrier at the edge of the tumor, in the peritumoral area.…”
Section: Figurementioning
confidence: 99%
“…Procedures are described in detail in the studies by Bauer et al (2007) and Hartz et al (2006). Briefly, freshly isolated brain capillaries in PBS buffer were transferred into Teflon microscope chambers with glass coverslip bottoms.…”
Section: Transport Assaysmentioning
confidence: 99%
“…Tumor necrosis factor-a-induced loss of P-glycoprotein activity is signaled through TNF-a receptor 1, endothelin-1 (ET-1), ET B receptor, nitric oxide synthase, and protein kinase C (PKC). The effect of TNF-a or ET-1 is mimicked by treatment with 10 nmol/L PMA (phorbol-12-myristate-13-acetate), and is prevented by treatment with 10 nmol/L BIM-1 (bis-indolylmaleimide), indicating involvement of a classic PKC isoform (a/b I/II /g) (Hartz et al, 2004(Hartz et al, , 2006.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations